Comparison of phenotypic methods and DNA hybridization for detection of methicillin-resistant Staphylococcus aureus. - Richard, P (1994)
One hundred thirty-eight Staphylococcus aureus isolates from patients with severe staphylococcal infections were collected in 15 French hospitals. Detection of the mec gene was performed by dot blot hybridization with a specific DNA probe. Dot blot results were used to characterize the isolates as methicillin susceptible (77 isolates) or resistant (61 isolates). The isolates were screened for methicillin resistance by an agar spread method on Mueller-Hinton plates containing oxacillin (2 and 10 micrograms/ml) and were incubated at 37 degrees C, with 10(8) CFU as the inoculum. MICs of oxacillin and methicillin were determined by the agar dilution method on Mueller-Hinton plates without NaCl, by using 10(5) CFU per spot, after 24 and 48h of incubation at 30 or 37 degrees C. Moderately elevated MICs were found for 20 isolates (14.5%). The mec gene was detected in six (30%) of the isolates expressing a low level of resistance to methicillin and/or oxacillin. As determined by comparison with probe hybridization results, the spread plate method with oxacillin at 2 micrograms/ml was more sensitive (sensitivity, 100%) and specific (specificity, 100%) than agar dilution with either methicillin or oxacillin in identifying methicillin resistance or susceptibility. Determinations of methicillin and oxacillin MICs by the agar dilution method had a specificity of 99 to 100% depending on the conditions of incubation, but the sensitivity was below 85% whatever the duration or temperature of incubation.